Outcome After Open Reduction Internal Fixation of Acetabular Fractures in the Elderly. Issue 3 (March 2022) - Sanders, Ethan; Finless, Alexandra; Adamczyk, Andrew; Dobransky, Johanna; Wilkin, Geoffrey; Gofton, Wade T.; Beaulé, Paul E.; Liew, Allan; Papp, Steven; Grammatopoulos, George
Abstract : Objectives: (1) Assess outcomes of acetabular open reduction and internal fixation (ORIF) in the elderly, (2) investigate factors influencing outcome, and (3) compare outcomes after low-energy and high-energy mechanisms of injury. Design: Retrospective case series. Setting: Level 1 trauma center. Patients: Seventy-eight patients older than 60 years (age: 70.1 ± 7.4; 73.1% males). Intervention: ORIF for acetabular fractures. Main Outcome Measurements: Complications, reoperation rates, Oxford Hip Score (OHS), and joint preservation and development of symptomatic osteoarthritis. Cases with osteoarthritis, OHS < 34, and those who required subsequent total hip arthroplasty were considered as poor outcome. Results: At a mean follow-up of 4.3 ± 3.7 years, 11 cases post-ORIF required a total hip arthroplasty. The 7-year joint survival post-ORIF was 80.7 ± 5.7%. Considering poor outcome as failure, the 7-year joint survival was 67.0 ± 8.9%. The grade of reduction was the most significant factor associated with outcome post-ORIF. Female sex ( P = 0.03), pre-existing osteoporosis ( P = 0.03), low-energy trauma ( P = 0.04), and Matta grade ( P = 0.002) were associated with poor outcome. Patients with associated both-column fractures were more likely to have nonanatomic reduction ( P = 0.008). After low-energy trauma, joint survivorship was 36.6 ± 13.5% at 7 years compared with 75.4 ± 7.4% in the high-energy group when considering poor outcome as an end point (log rank P = 0.006). The cohort's mean OHS was 37.9 ± 9.3 (17–48). Conclusions: We recommend ORIF whenever an anatomic reduction is feasible. However, achievement and maintenance of anatomic reduction are a challenge in the elderly, specifically in those with low-energy fractures involving both columns, prompting consideration for alternative management strategies. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.